Yellow‐eyed piranhas produce louder sounds than red‐eyed piranhas in an invasive population of Serrasalmus marginatus. Issue 6 (5th October 2020) - Raick, Xavier; Huby, Alessia; Kurchevski, Gregório; Godinho, Alexandre L.; Parmentier, Éric
Abstract: Serrasalmus marginatus is a piranha species native from the lower Paraná River basin and has been invasive in the upper Paraná River basin since the 1980s. In piranhas, sounds of different species have different features. The aim of this study was to investigate if the sounds produced by this species could be used to distinguish two morphotypes: red‐ and yellow‐eyed S. marginatus from the Araguari River (upper Paraná River basin). All the temporal and frequency features of the sounds were equivalent in both groups of eye colour; it corresponds to the species‐specific signature described for S. marginatus . Nonetheless, the amplitude features were all statistically different between red‐ and yellow‐eyed piranhas. Yellow‐eyed specimens produced louder sounds. In different fish species, colour change in eyes can be due to the absence or the presence of a dominant allele. It can also be involved in social rank or during reproduction. Different hormones and neuropeptides can modulate vocal features. It is hypothesized that a mutation or different hormonal concentrations could explain both sound amplitude and eye colour playing a role in animal communication in S. marginatus .